A Novel Low-RCS and Wideband Circularly Polarized Patch Array Based on Metasurface - X. W. Zhu; J. Gao; X. Y. Cao; T. Li; Y. J. Zheng; L. L. Cong; L. R. Ji-Di; B. W. Zhu (Radioengineering, 2019)
In this paper, a novel circularly polarized (CP) array antenna based on metasurface (MS) is designed to realize wideband radar cross section (RCS) reduction, wideband operation and high gain. The MS is composed of compact polarization-dependent artificial magnetic conductors (PDAMCs), by regularly arranging the PDAMCs like chessboard directly on the top of the patch antenna, the MS can significantly bring RCS down. On the other hand, due to the compact structure of MS and the driven array patches, surface wave propagates on the MS and generates additional resonances to achieve wide operation band and high gain. Both the simulated and measured results indicate that the RCS at bore-sight is reduced more than 6dB from 5.08 GHz to 11.46 GHz (77.15%) except for some frequency points, The antenna yielded a good broadside left-hand CP radiation, the ǀS11ǀ<-10 dB impedance bandwidth is from 5.03 GHz to 7.4 GHz (38.13%) and the 1-dB axial ratio bandwidth is from 4GHz to 8GHz. Both the radiating and scattering performances have been obviously improved.